Paediatric formulations—part of the repurposing concept? - Wang, Siri; Giannuzzi, Viviana (Frontiers in Medicine, 2024)
The lack of available appropriate paediatric formulations is a significant challenge for optimal treatment in children. The resulting manipulation of adult medicines implies risk of medication errors, inaccurate dosing, and unacceptable dosage forms resulting in non-compliance. This represents significant unmet needs for a large and vulnerable patient group.Currently, the repurposing discussions seems only to a limited degree to cover the aspects of paediatric off-label use of adult medicines, including reformulation strategies to cover unmet needs for suitable formulations in the youngest age groups. Similarly, limited focus seems to be put on incentives in this specific area of repurposing. This paper will discuss the role of reformulation for paediatric needs as part of the repurposing concept, and potential factors contributing to barriers to incentivise the development of new formulations for children.